2014
DOI: 10.1111/jopr.12186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Hydrogel Patch on Denture‐Related Traumatic Ulcers; an Exploratory Study

Abstract: The results of this exploratory study suggest that application of hydrogel patches may represent a novel, effective treatment for accelerating the healing process and pain reduction in mucosal lesions associated with complete dentures also in people with type 2 diabetes; however, larger studies need to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Age is a factor that can predispose to appearance and adversely affect healing of oral lesions, since it is usually associated with concomitant diseases and the chronic use of medication. 13 The senescence process is also directly associated with morphological changes in the oral cavity. The stratified squamous epithelium becomes thinner, loses elasticity, and atrophies with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age is a factor that can predispose to appearance and adversely affect healing of oral lesions, since it is usually associated with concomitant diseases and the chronic use of medication. 13 The senescence process is also directly associated with morphological changes in the oral cavity. The stratified squamous epithelium becomes thinner, loses elasticity, and atrophies with age.…”
Section: Discussionmentioning
confidence: 99%
“…In their study did not performed measurement of minimum and maximum size of ulcers, neither for perimeter and area. 13 On the other hand, Alzarea et al. examined the effect of ozon in the treatment of denture-related ulcers, and they found that the maximum ulcer size was about 8 mm, while the minimum ulcer size was about 3.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removable dentures are the most common treatment choice in edentulous patients. İn most cases edentulocity is accompanied with thinner epithelium, reduced resilience and reduced capacity for tissue regeneration as an effect of aging process [10]. Due to different systematic diseases, use of tobacco, use of xerogenic medications, poor oral hygiene oral mucosa , consequently becomes more vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Usual care for denture-associated traumatic ulcers demand adjustment of the margins and occlusal adaptation of the dentures [10], accompained with symotomatic (pain relife) therapy combined with instruction in home denture hygiene and careful observation.…”
Section: Discussionmentioning
confidence: 99%